Factors influencing the characteristics and distribution or surface organic matter in the Pacific-Atlantic connection - Barrera, Facundo (2017)
The present work reports the first data set on particulate organic carbon (POC) and nitrogen (PON), and the high-resolution modelling of their stable isotope variability in the Patagonian Cold Estuarine System (PCES), with focus on particulate organic matter (POM) origin and distribution in dependence on physical, chemical and biological parameters. POC, PON, stable carbon (δ¹³C) and nitrogen isotopes (δ¹⁵N), dissolved organic nitrogen, phaeopigments, diatom, dinoflagellate and heterotrophic bacteria (HB) abundance are reported for 17 stations in different waters masses in the southern end of the Argentine shelf in late summer 2012. Most parameters denote clear differences between Beagle - Magellan Water (BMW), Subantarctic Shelf Water (SSW) and Subantarctic Water (SAW). POC and PON decreased from maxima in BMW to intermediate values in SSW and minima in SAW. There was a highly significant correlation among POC, PON and fluorescence indicators of diagenetic maturity of dissolved humic matter. This, together with the inverse correlations of salinity with POC and PON, and the wide range of C:N ratios indicate that POM in the study area is partly derived from terrestrial runoff, superimposed by autochthonous components from plankton of different life stages. HB abundance was significantly correlated with POC and dissolved organic matter (DOM), likely reflecting a resource control of HB and a significant contribution of bacterial biomass to POM in the nanoparticle fraction. The direct relationship between HB and dissolved humics suggests bacterial uptake of DOM fractions otherwise considered refractory. POM complexity was reflected in a wide variation of δ¹³C, despite the narrow temperature range of this region. The variability of stable isotopes of POC could be accounted for by a model with a degree of detail hitherto not reported in the literature. A multiple regression including C:N ratio, ammonium and the quotient between log abundance of diatoms, dinoflagellates and HB explained 92% of δ¹³C variance, mostly produced by ammonium. Despite the strong effect of ammonium on δ¹³C, δ¹⁵N variability was largely explained by a strong inverse relationship with the fraction of unutilized nitrate, suggesting dominance of nitrate uptake. However, the proportion of presumably isotopically heavier ammonium derived from continental runoff in the marine δ¹⁵N-POM pool is unknown and requires investigation of the isotopic composition of dissolved inorganic nitrogen in the PCES. The presented new information and its comparison with data from other sectors of the Argentine shelf constitute a contribution to an approach for the understanding of the organic matter dynamics that can be potentially expanded to the entire Southwest Atlantic.